Narrative and its nonevents: the unwritten plots that shaped Victorian realism - Glatt, Carra (Victorian literature and culture series, 2022)
"In Narrative and Its Nonevents, Carra Glatt argues for the central role of non-actualized or "unwritten plots" in Victorian narrative construction. Abandoning the allegorical mode, in which characters are bound by fixed identities to reach a predetermined conclusion, and turning away from classical and historical plots with outcomes already known to audiences, the realist novel of the Victorian Era is designed to simulate the openness and uncertainty of ordinary human experience. We are invested in the stories of a Crusoe or Pamela or Tom Jones in part because we can't be entirely sure how those stories will end. As Glatt demonstrates, the Victorian novel is characterized by a proliferation of possibilities"--